Komunikasi Interpersonal Pengajar Dalam Membentuk Kepribadian Peserta Usia 5-12 Tahun Studi Pada TPQ Baiturrahman Kelurahan Makbalim - Vani, Radita; Ahriani, Andi (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
This research aims to determine the role of teachers' interpersonal communication in shaping the personality of students aged 5-12 years at TPQ Baiturrahman, Makbalim Village. At this stage of development, children are at a crucial phase in the formation of personality and moral values. Communication carried out by teachers not only functions as a medium for conveying knowledge, but also as an important means of directing and shaping children's personalities. Through daily interactions, teachers have the opportunity to instill positive values ​​that can shape students' personalities. This research uses a qualitative approach with observation and interview methods to understand how teachers communicate with students and its impact on the formation of their personalities. Research findings show that teachers who use an empathetic, assertive and supportive interpersonal communication approach tend to be more successful in building positive relationships with students. This contributes to increasing self-confidence, positive attitudes, and the formation of strong moral values ​​in children. The results of this research indicate that effective interpersonal communication between teachers and students is very important in forming the personality of children aged 5- 12 years old